Three Novel Breast Cancer Genes: A Proteomic and Genomic Study - Ashokan K. V. (International Journal of Research in Chemistry and Environment (IJRCE), 2011)
Breast cancer is a heterogeneous disease. Many genes are involved in breast cancer and most of them are express the cancer property by mutation. Recently three novel genes have been discovered in relation to breast cancer. The three genes-C6ORF96, C6ORF97 and C6ORF211 has not been studied widely so far. Hence, in this paper I try to annotate the physicochemical properties, and other parameters of the genes translational proteins. The physicochemical properties like isoelectric point, GRAVY, instability index, hydrophobicity, antigenicity, extinction coefficient and charges were studied. It will help to study the protein further in the cancer research. The paper also exposed the amino acid percentage, which will assists in further research in cancer proteomics. The study also concentrated on multiple sequence alignment and gene interaction with other genes of the vicinity. The gene functional interaction revealed interesting factors like C6ORF96 has no physical interacting gene related. While the c6ORF97 and C6ORF211 shows well marked physical interacting genes, hence a further study concentrating on the interacting genes along with C6ORF97 and C6ORF211 genes should be promoted to understand more about the breast cancer therapy.